2007
DOI: 10.1016/j.jom.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain practice and information sharing

Abstract: Effective supply chain practice and information sharing enhances the current supply chain management environment. The purpose of this study is to investigate the integration of information sharing and supply chain practice in supply chain management. Data from 125 North American manufacturing firms were collected. The results show that (1) effective information sharing significantly enhances effective supply chain practice; (2) supply chain dynamism has significant positive influence on effective information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
576
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(611 citation statements)
references
References 36 publications
21
576
1
13
Order By: Relevance
“…The results of this research are consistent with the findings of prior studies in IS. However, the impact of processing has mentioned in the literature to have a an effect on user satisfaction [41], content has a direct effect on user satisfaction in studies conducted by Maditinos and Theodoridis [47], additionally, usability showed a significant relationship with satisfaction in recent study by Belanche, Casaló [65], furthermore, studies by Guimaraes and Igbaria [53] and Hou [24] found that user satisfaction has strong direct influence on users performance. The results of this study prove the importance of processing, content and usability in enhancing and boosting end users satisfaction and as a result improving individual performance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this research are consistent with the findings of prior studies in IS. However, the impact of processing has mentioned in the literature to have a an effect on user satisfaction [41], content has a direct effect on user satisfaction in studies conducted by Maditinos and Theodoridis [47], additionally, usability showed a significant relationship with satisfaction in recent study by Belanche, Casaló [65], furthermore, studies by Guimaraes and Igbaria [53] and Hou [24] found that user satisfaction has strong direct influence on users performance. The results of this study prove the importance of processing, content and usability in enhancing and boosting end users satisfaction and as a result improving individual performance.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, the use of e-catalogue reduces processing time needed to place an order [39]; consequently, using e-procurement systems decrease user compliant by minimizing errors and improving the match between user need and products received [40]. Zhou and Benton Jr [41] stated that in order to improve organizational performance and thus users satisfaction, organizations should leverage their dynamism by increasing information processing capacity. System processing influences user satisfaction when, "the perception of users that the system effectively meets their business demands" [40].…”
Section: Factors Influencing User Satisfactionmentioning
confidence: 99%
“…In hierarchical decision making structures, information is not automatically made available for all agents, which may result in a certain degree of local optimization. This appears to be rather typical in transport chains today, since often only a limited amount of information is shared (Zhou and Benton Jr., 2007).…”
Section: The Simulation Modelmentioning
confidence: 98%
“…With enterprise technology, users are able to improve operational efficiency through measures such as increasing standardization or tightening process control. Furthermore, the exploitation approach tends to result in operational benefits such as lead time reduction and inventory accuracy [5]. Firms oriented to exploitation, use enterprise information technology for information sharing, channel collaboration, and integrated forecasting and inventory replenishment.…”
Section: Adaptive Process Concept Toward Enterprise Information Technmentioning
confidence: 99%
“…Planning collaboration (F3) and forecasting and replenishing coordination (F4) are considered as supply chain collaboration measures. Collaboration and coordination in planning is defined as jointly plan for supply chain key activities [3] [4]; while operational collaboration and coordination are defined as information sharing to achieve efficient task execution [5]. Operational benefits (F5) are defined as first-order benefits that…”
Section: Introductionmentioning
confidence: 99%